2013
DOI: 10.1124/dmd.112.050054
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Sequestration (Trapping) of Lipophilic Amine (Cationic Amphiphilic) Drugs in Immortalized Human Hepatocytes (Fa2N-4 Cells)

Abstract: Lipophilic (logP > 1) and amphiphilic drugs (also known as cationic amphiphilic drugs) with ionizable amines (pK a > 6) can accumulate in lysosomes, a process known as lysosomal trapping. This process contributes to presystemic extraction by lysosome-rich organs (such as liver and lung), which, together with the binding of lipophilic amines to phospholipids, contributes to the large volume of distribution characteristic of numerous cardiovascular and central nervous system drugs. Accumulation of lipophilic ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 35 publications
11
195
0
Order By: Relevance
“…Almost all (95%) of Gleevec entering cells (regardless of cell type) becomes sequestered in lysosomes (25,26) through ion trapping, because Gleevec is a weak base (27)(28)(29). To examine the possibility that Gleevec might inhibit the activities of lysosomal proteases by raising lysosomal pH, we exposed N2a 695 cells to vehicle or to Gleevec for 4 h and then to the lysosomotropic dye Lysotracker Red (Thermo Fisher Scientific), which sequesters in acidified lysosomes (30).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all (95%) of Gleevec entering cells (regardless of cell type) becomes sequestered in lysosomes (25,26) through ion trapping, because Gleevec is a weak base (27)(28)(29). To examine the possibility that Gleevec might inhibit the activities of lysosomal proteases by raising lysosomal pH, we exposed N2a 695 cells to vehicle or to Gleevec for 4 h and then to the lysosomotropic dye Lysotracker Red (Thermo Fisher Scientific), which sequesters in acidified lysosomes (30).…”
Section: Resultsmentioning
confidence: 99%
“…For example amodiaquine and chloroquine are well known antimalarials, clomiphene and toremifene are selective estrogen receptor modulators, while amiodarone, dronedarone, and verapamil are anti-arrhythmics 4 . It may or may not be of importance but all of these compounds have a common tertiary amine feature 10, 11 . What is important is that they are all orally bioavailable and generally safe for humans at their approved doses.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that VP35 may be a potential target for these two distinct classes of compounds. However, it is important to point out that we have not compared docking to other proteins in EBOV and it could also be possible that these molecules are active elsewhere as well as via other mechanisms than by specific binding to proteins 28, 29 . Further, VP35 may be a preferred target for the antimalarials while the SERMs are not predicted to bind as well as the X-ray ligand.…”
Section: Discussionmentioning
confidence: 99%